WEBSITE DESIGN APPLICATIONS ON FORUM AL-HIKMAH LDK USING APPLICATIONS CONTENT MANAGEMENT SYSTEM (CMS) PhpBB 3.0.1 - Rizki Zulfika; Elly Agustina J, SKom., MMSI (Jurnal Sistem Informasi, 2008)
As one of the Student Activity Unit of the Islamic missionary activities in spreading STMIK Jakarta, Lembaga Dakwah Kampus (LDK) Al-Hikmah require a medium to further increase the Islamic activity in the campus environment and society. Therefore, the forum was established website which can simplify and more attractive in the delivery of Islamic activity. To build this forum website, the author using an application content management system (CMS) called PhpBB version 3.0.1. This is because the features of the website which attracts more users such as chat and forum questions and answers that enable users to use more interactive Internet services.